Diversity of earthworms (Oligochaeta: Lumbricidae) in Sofia Plain, Bulgaria - Hristo (ZooNotes, 2014)
A rich earthworm material from 47 different localities in Sofia Plain has been elaborated. During the investigations between the years 2010 and 2013, thirteen earthworm species and subspecies were collected altogether, belonging to seven genera. Among them, three new records are reported. Aporrectodea longa (Ude, 1885), Eisenia lucens (Waga, 1857) and Octodrilus transpadanus (Rosa, 1884) proved to be new to the earthworm fauna of Sofia plain.